Computational methods and experimental measurements XV - International Conference on Computational Methods and Experimental Measurements (15th : 2011 : Wessex Institute of Technology, New Forest, UK); Carlomagno, G. M.; Brebbia, C. A.; Wessex Institute of Technology; Universit d̉i Napoli (Southampton : WIT Press)
Containing edited versions of most of the papers presented at the Fifteenth International Conference on Computational Methods and Experimental Measurements, this book reviews the latest work on these two approaches, and the interaction between them.